2018
DOI: 10.4236/gep.2018.61003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Weather Research and Forecasting (WRF) Model Parameterization Schemes Skill to Simulate Extreme Rainfall Events over Dar es Salaam on 21 December 2011

Abstract: This paper evaluates the skills of physical Parameterization schemes in simulating extreme rainfall events over Dar es Salaam Region, Tanzania using the Weather Research and Forecasting (WRF) model. The model skill is determined during the 21 December 2011 flooding event. Ten sensitivity experiments have been conducted using Cumulus, Convective and Planetary boundary layer schemes to find the best combination and optimize the WRF model for the study area for heavy rainfall events. Model simulation results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When we consider the outperforming PBL, the scheme that was designed for unstable conditions in the PBL, such as ACM2, outperforms in this study. A similar study in the tropical region by [62] also indicated that the KF cumulus parametrization scheme and ACM2 PBL, in combination with Lin microphysics, perform better in simulating heavy rainfall events in Tanzania. In their study, however, the use of GF and ACM2 in combination with WSM6 shows poor results with high error scores.…”
Section: Discussionmentioning
confidence: 75%
“…When we consider the outperforming PBL, the scheme that was designed for unstable conditions in the PBL, such as ACM2, outperforms in this study. A similar study in the tropical region by [62] also indicated that the KF cumulus parametrization scheme and ACM2 PBL, in combination with Lin microphysics, perform better in simulating heavy rainfall events in Tanzania. In their study, however, the use of GF and ACM2 in combination with WSM6 shows poor results with high error scores.…”
Section: Discussionmentioning
confidence: 75%
“…Their study, however, investigates a range of grid lengths down to 12 km only. Ngailo et al (2018) also found Kain-Fritsch to be the best performing cumulus scheme for extreme precipitation in Tanzania, where Grell-Freitas produced very high MAEs. Encouraging results with Grell-Freitas were found by (Fowler et al 2016) on a variable-resolution mesh centered over South Africa.…”
Section: Discussionmentioning
confidence: 82%
“…The study area is characterized by having two main seasons. The dry season starts from June to August and the rainy season starts from March to May (Ngailo et al 2018). The city comprises an estimated population of 6.4 million with a growth rate of 5.29% (NBS 2017).…”
Section: Methodology Description Of Study Areamentioning
confidence: 99%